2020
DOI: 10.2174/1568026619666191116160908
|View full text |Cite
|
Sign up to set email alerts
|

The Cytoprotective and Anti-cancer Potential of Bisbenzylisoquinoline Alkaloids from Nelumbo nucifera

Abstract: : Natural product therapy has been gaining therapeutic importance against various diseases, including cancer. The failure of chemotherapy due to its associated adverse effects promoted adjunct therapy with natural products. Phytochemicals exert anti-carcinogenic activities through the regulation of various cell signaling pathways such as cell survival, inflammation, apoptosis, autophagy and metastasis. The ‘small molecule-chemosensitizing agents’ from plants induce apoptosis in drug-resistant and host-immune r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 83 publications
0
19
0
Order By: Relevance
“…Interestingly, it exhibits the reversal of multi‐drug resistance in cancer cells (Kadioglu et al, 2017). Nef was also shown to inhibit pyroptosis in kidney cells (Tang et al, 2019) and has been suggested to provide protection against cell death in muscle cells, cardiovascular diseases, and neurological diseases (Baskaran, Poornima, Huang, & Padma, 2016; Manogaran, Beeraka, & Padma, 2019). In case of cancer, Nef was demonstrated to induce reactive oxygen species (ROS)‐dependent mitochondrial‐mediated apoptosis in liver, lung, breast, cervical, and osteosarcoma cancer cells (Eid & Abdel‐Rehim, 2017; Poornima, Quency, et al, 2013; Poornima, Weng, et al, 2013; Yang et al, 2016; Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it exhibits the reversal of multi‐drug resistance in cancer cells (Kadioglu et al, 2017). Nef was also shown to inhibit pyroptosis in kidney cells (Tang et al, 2019) and has been suggested to provide protection against cell death in muscle cells, cardiovascular diseases, and neurological diseases (Baskaran, Poornima, Huang, & Padma, 2016; Manogaran, Beeraka, & Padma, 2019). In case of cancer, Nef was demonstrated to induce reactive oxygen species (ROS)‐dependent mitochondrial‐mediated apoptosis in liver, lung, breast, cervical, and osteosarcoma cancer cells (Eid & Abdel‐Rehim, 2017; Poornima, Quency, et al, 2013; Poornima, Weng, et al, 2013; Yang et al, 2016; Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous reviews mainly focused on traditional and ethnopharmacological uses, biosynthesis, phytochemical analysis, industrial applications, and broad-spectrum health benefits of N. nucifera in which an overview of anticancer potential represents a minor representation [29,[31][32][33][34]37]. Several prior publications highlighted pharmacological activities of selected phytochemicals of N. nucifera, and these reports did not have a sole focus on cancer [25,35,36,38,39]. Hence, the aim of this work has been to perform a systematic and critical analysis of fragmentary studies to provide an up-to-date and complete assessment of cancer-preventive and anticancer therapeutic attributes of N. nucifera and its bioactive phytocomponents with an understanding of the cellular and molecular mechanisms of action.…”
Section: Introductionmentioning
confidence: 99%
“…Manogaran et al. 29 reported that anti-cancer activity of Nef was achieved through enhanced activation of MAP kinases, ROS generation, followed by induction of apoptotic and autophagy cell death. In this study, we found that Nef treatment prevented invasion, inhibited angiogenesis, and reduced vascular endothelial growth factor expression of WERI-Rb-1 cell.…”
Section: Discussionmentioning
confidence: 99%